Effects of Y-balance and aero-step training on balance ability and muscle activity in young adults - Choi, Jung-Hyun (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The Y-Balance test has been used in several studies to evaluate the training effects, performance enhancement, and postural control in athletes. In the present study, we aimed to investigate the effects of a training program, which includes the Y-Balance test and aero-step, on balance ability and lower limb muscle activity in young adults.Methods/Statistical analysis: We recruited 24 healthy adults: 12 assigned to the Y-Balance training group (YBTG) and 12 assigned to the aero-step training group (ATG). We analyzed the balancing ability and the activation of the tibialis anterior and peroneus longus muscles before and after training within and between each intervention group. The respective training programs were conducted for 5 weeks, 3 sessions per week, 40 minutes per session.Findings: In YBTG, the subjects’ ability to balance was significantly increased (p